2009
DOI: 10.1002/elps.200800405
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic analysis of WGA‐bound glycoprotein biomarkers in sera from patients with lung adenocarcinoma

Abstract: Differential protein expression profiles in the serum samples from patients with lung adenocarcinoma may be associated with glycosylation during cancer development. In this study, we used various glycoproteomic approaches to investigate the different glycoproteomic profiles of human normal and lung adenocarcinoma serum samples and to investigate putative altered glycoprotein biomarkers. In our preliminary screening, FITC-labeled lectin staining was used for the detection of specific glycoprotein profiles. whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 60 publications
2
72
0
1
Order By: Relevance
“…Proteins that contain the desired glycans were enriched from cell lysates or a protein mixture and quantitatively analyzed by mass spectrometry. Glycoproteomic approaches have been applied to identify new tumor markers (25,41,42). In this study, we successfully identified 16 EV71-interacting proteins by glycoproteomic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins that contain the desired glycans were enriched from cell lysates or a protein mixture and quantitatively analyzed by mass spectrometry. Glycoproteomic approaches have been applied to identify new tumor markers (25,41,42). In this study, we successfully identified 16 EV71-interacting proteins by glycoproteomic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…WGA lectin affinity, for example, was used to enrich glycoproteins in serum samples and then gel electrophoresis and MS analysis was used to identify 39 differentially expressed proteins and suggested as possible biomarkers in lung cancer development and progression. WGA was found to capture more glycoproteins from the serum samples than six other lectins that were tested [186]. The immobilization of lectins on monolithic support was mostly done by covalent binding of amines on lysine residues to aldehyde-functionalized surfaces.…”
Section: Lectin Affinitymentioning
confidence: 99%
“…Byly nalezeny tři glykoproteiny ve zvýšené koncentraci (adiponektin, ceruloplasmin a glykofosfatidyl-inositol-80) a dva glykoproteiny ve snížené koncentraci (cyclin H a Fyt) přímo související s vývojem adenokarcinomu plic, které by mohly být užitečné pro včasnou detekci onemocnění nebo sledování jeho progrese [47].…”
Section: Závěrunclassified